2016
DOI: 10.1042/bsr20160229
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of neointima formation by targeting β-catenin/TCF pathway

Abstract: Coronary artery disease is treated by vein grafting and stent implantation. Late vein graft failure and restenosis of stented arteries reduce the success rates of these approaches and are caused by neointima formation. We have previously shown that Wnt proteins are up-regulated during intimal thickening, and have speculated that these lead to activation of downstream genes with β-catenin/T-cell factor (TCF)-responsive promoters. In the present study, we aimed to provide evidence that β-catenin/TCF signalling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…We have previously shown that Wnt/β-catenin/TCF-activated VSMCs display higher migratory and proliferative rates and thereby contribute to intimal thickening 6, 7. Williams et al 4 . demonstrated that Ad-mediated delivery of the thymidine kinase (TK) gene driven by a Wnt/β-catenin/TCF-responsive promoter suppressed neointima formation in ligated carotid arteries of mice infused with ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that Wnt/β-catenin/TCF-activated VSMCs display higher migratory and proliferative rates and thereby contribute to intimal thickening 6, 7. Williams et al 4 . demonstrated that Ad-mediated delivery of the thymidine kinase (TK) gene driven by a Wnt/β-catenin/TCF-responsive promoter suppressed neointima formation in ligated carotid arteries of mice infused with ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that overexpression of dominant-negative N-cadherin (dn-N-cadherin), which consists of amino acids 6–27 (the cytoplasmic and transmembrane domains), in isolated VSMCs promoted apoptosis and reduced intimal thickening ex vivo 3 . We have also identified Wnt/β-catenin/T cell factor (TCF) signaling as a modulator of VSMC phenotype and contributor to intimal thickening 3, 4. In consideration of our previous findings, we have developed an adenovirus (Ad)-based vector, in which the pro-apoptotic dn-N-cadherin gene was driven by a Wnt/β-catenin/TCF-responsive promoter linked to a minimal cytomegalovirus (CMV) promoter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…144 Two recent studies using the mouse carotid artery ligation model demonstrated that selective suicide of cells with active Wnt signalling retards intimal thickening. 145,146…”
Section: Cell-cell Contacts-cadherinsmentioning
confidence: 99%